The Prevent Duty in Education 2020
DOI: 10.1007/978-3-030-45559-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Student Perspectives on Teaching and the Prevent Policy

Abstract: In this chapter we shift our focus away from adults enacting policy to consider how young people think schools can help them to develop their knowledge and understanding of terrorism and extremism. The evidence suggests that young people generally support the values of democracy and reject the use of political violence, but they want their teachers to develop critical media and political literacy and trust them to explore multiple perspectives. Our review of government-endorsed educational resources concludes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In earlier work examining a small selection of classroom resources (Elwick et al, 2020) we concluded that they often fell short of providing young people with developed, critical and nuanced knowledge to help them counter extremism. We found the resources often over-simplified these complex subjects and reproduced stereotypes.…”
Section: A Human Rights Approach?mentioning
confidence: 95%
See 1 more Smart Citation
“…In earlier work examining a small selection of classroom resources (Elwick et al, 2020) we concluded that they often fell short of providing young people with developed, critical and nuanced knowledge to help them counter extremism. We found the resources often over-simplified these complex subjects and reproduced stereotypes.…”
Section: A Human Rights Approach?mentioning
confidence: 95%
“…Those persons reading them to inform their own actions similarly have the capacity to engage in a readerly and writerly role, and therefore such an analysis cannot yield insights into how children actually experience the policy. Our previous work, reporting on young people's views, emphasised that students want an educational opportunity to learn about and improve their understanding of terrorism and violent extremism, as media coverage sometimes leaves them feeling overwhelmed and confused (Elwick, Jerome & Svennevig, 2020). This analysis aims to provide some indication about the extent to which this is achieved in the resources on offer.…”
Section: Methodsmentioning
confidence: 99%
“…If the Prevent policy positions teachers as agents of surveillance, then young people are positioned as vulnerable and needing protection, particularly those from Muslim communities. Elwick et al (2020) draw on empirical research with young people to conclude that Muslim students experience the teaching of fundamental British values (FBV) as exclusionary, discriminatory, and intimidating (Elwick et al, 2020, p. 61). They also found that "young people want to learn about terrorism and extremism to build their religious, political and critical media literacy" and counteract the brainwashing of the media (Elwick et al, 2020, p. 61).…”
Section: Muslims As a Suspect Communitymentioning
confidence: 99%
“…Young people in Elwick et al's study (2020) emphasized the importance of the teacher providing the full story rather than one-sided view from the media. Governmental resources such as *Educate Against Hate[https://educateagainsthate.com/]*, which aim to teach FBV, were criticized by Elwick et al (2020). They claim such resources reduce the teacher to an uncritical promoter of predetermined answers rather than allowing them to develop their professionalism as a facilitator for debates about the motives of terrorists and support young people in critiquing behaviors and motives and helping them to appreciate the complexities of democracy, tolerance, and mutual respect.…”
Section: Muslims As a Suspect Communitymentioning
confidence: 99%